2021
DOI: 10.36923/jicc.v21i3.21
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Living Together, the Integration and Recognition of Self and Other: Applied Intercultural Ethics

Abstract: Rising global multidimensional migration has altered human/cultural interaction where one now needs to welcome another and the other needs to be welcome. Notwithstanding the intensified interaction, the resulting intercultural paradigm encounters myriad dehumanizing, alienating and subjugating challenges. While juxtaposing Europe’s and Quebec’s intercultural experiences, this article examines these challenges as fallouts of the difficulties or the unwillingness to complement the integration and recognition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…This idea focuses, in particular, on how various cultural groups perceive, interpret, and represent reality in the form of words or language. Ethnolinguistics from a social-anthropologist perspective studies the life and culture of social or ethnic groups, including conventions, customs, lifestyles, laws, art, literature, traditions, religion, and language (Davis et al, 2021;Dine, 2021;Haris & Ukkas, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea focuses, in particular, on how various cultural groups perceive, interpret, and represent reality in the form of words or language. Ethnolinguistics from a social-anthropologist perspective studies the life and culture of social or ethnic groups, including conventions, customs, lifestyles, laws, art, literature, traditions, religion, and language (Davis et al, 2021;Dine, 2021;Haris & Ukkas, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sanatifar, S. & Ayob (2022) also suggested that a language's lexicon reflects its cultural environment. In other words, cultural semantics translate the meaning of expressions so that the knowledge system is known and reflected in the mindset view of life and worldview of the cultural context in society (Dine, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%